Real‐world direct oral anticoagulant experience in atrial fibrillation: falls risk and low dose anticoagulation are predictive of both bleeding and stroke risk. Issue 11 (20th November 2020) - Brook, Rowena; Aswapanyawongse, Oranut; Tacey, Mark; Kitipornchai, Tanun; Ho, Prahlad; Lim, Hui Y.
Abstract: Background: Clinical trials have demonstrated that direct oral anticoagulants (DOAC) are non‐inferior to vitamin K antagonist for stroke prevention in non‐valvular atrial fibrillation (AF) with comparable safety outcomes; however, real‐world Australian data are limited. Aims: To evaluate local real‐world DOAC use focussing on safety, particularly in high‐risk patients. Methods: A retrospective evaluation of 658 patients commenced or continued on DOAC between September 2013 and September 2016 for non‐valvular AF at Northern Hospital, a tertiary hospital in Victoria, Australia was performed. Results: Factor Xa inhibitors were more commonly prescribed than direct thrombin inhibitors (83.3 vs 16.7%) for AF management. The median patient age was 75 years. The rate of clinically significant bleeding on anticoagulation was 3.13 per 100 person‐years (including four deaths) with risk factors including history of bleeding (hazard ratio (HR) 3.52, 95% confidence interval (CI) 1.22–10.17), concurrent antiplatelet therapy (HR 2.62, 95% CI: 1.11–6.20) and high falls risk (HR 2.76, 95% CI: 1.26–6.08). Patients on low‐dose DOAC had significantly higher bleeding risk compared with those on full dose (5.05 vs 1.82 per 100 person‐years). The rate of thrombotic stroke despite anticoagulation was 1.34 per 100 person‐years with risk factors including low dose anticoagulation ( P = 0.034), high falls risk ( P = 0.046) and previous stroke ( P = 0.028). Conclusions: DOAC use in real‐world Australian practice is safe and effective, consistent with international data. Low dose anticoagulation and falls risk are associated with increased bleeding and thrombotic risk demonstrating overlapping risk factors. Careful individualised patient risk assessment is still required as low dose anticoagulation is not without risks.